The Effects of COVID-19 outbreak on the Nigerian Stock Exchange performance: Evidence from GARCH Models - Monday Osagie Adenomon; Bilkisu Maijamaa; Daniel Owoicholofu John (Journal of Statistical Modeling and Analytics (JOSMA), 2022)
The recent COVID-19 was first identified in Wuhan, China in December 2019 and now it has caused huge death and spread to almost all over the world. There are news that most of the world economy and financial markets would be affected due to protocols such as lockdown and social distancing. In Nigeria, the first case of COVID-19 was identified on 27th February 2020 and this present study examines the effect of COVID-19 outbreak on the performance of the Nigeria stock exchange using secondary data for the period of 2nd March 2015 to 16th April, 2020. Also the study considered the COVID-19 period of 2nd January 2020 to 16th April 2020, the results from GARCH models revealed a loss in stock returns and high volatility in stock returns under the COVID-19 period in Nigeria as against the non COVID-19 period. Also, the Quadratic GARCH (QGARCH) and Exponential GARCH (EGARCH) models with dummy variable were applied to the stock returns which shown that the COVID-19 has had negative effect on the stock returns in the Nigeria stock markets. The study therefore recommended that economic policy such as incentive to indigenous companies to create new employments, diversification of the economy to attract new investors, and flexible exchange rate regime that will aid business between Nigeria investors and the international market (trade) be implemented. Lastly, the government of Nigeria should ensure policy that ensures stable political environment and reduction in insecurity in the country.